Environmental sustainability and social cost-benefit evaluations of bioCNG as a fuel for transportation in the context of South African Provinces - Moshood Akanni Alao; Olawale Muhammed Popoola (Sustainable Futures)
Decarbonization through the use of low-carbon fuel such as bio-compressed natural gas (bioCNG) in transport sector could play a major role in the transition to net-zero, climate change mitigation and circular economy. This study investigates the environmental sustainability potential and social cost-benefits of bioCNG as a transport fuel for South African provinces. A net-zero emission technique was adopted for evaluating environmental sustainability while the cost-benefit of social externalities was modelled using willingness-to-pay technique. Additionally, sensitivity analysis was performed to look at how various assumed variables affected the study's overall outcome. The findings show that, under the current scenario of waste landfilling, an estimated 5869.809 ktonCO2eq/year of carbon emissions would be emitted into the environment. However, utilizing the generated waste for bioCNG production, a total of 2341 million kg of bioCNG is produced which is capable of filling >460 million 5 kg gas cylinders for automobile application with an estimated emission mitigation of 1377.63 ktonsCO2eq/year which corresponds to 0.29 % of 2020 South African emission portfolio. Considering all the emission pathways, the estimated resultant social cost-benefit savings of 10.41 billion USD/year was obtained which is equivalent to 28 % of the 2024/2025 of South African national budget for the combined expenditure on social protection and healthcare. This research provides an insight into the role that the waste-to-bioCNG supply chain plays in achieving SDGs 3, 11, and 13. The proposed methodology could be extended to other countries particularly in Sub-Saharan Africa with similar waste composition and economic activities.